Processing of fish protein concentrate by using saline concentrates and study some of its quality - Al-Hassoon, Ahmed Sh. (Iraqi Journal of Aquaculture, 2022)
The aim of this investigation is to process a fish protein concentrate from a freshwater fish Tilapia zilli , the fish brought from local Basrah market , some of it minced , and the rest dried in the oven at 70 °c for 48 hr. , a saline solutions of 1% and 2% had been used to hydrolyze the fish flesh . The chemical composition of the fish were 56.86 % protein (N× 6.25) ,19.13% fat and 18.11% , while for the processed protein concentrates were 77.40% , 85.05% protein (N× 6.25) ,10.58% , 6.00% fat and 5.41% , 6.13% ash for the two saline concentrates 1% and 2% respectively . The obtained yield was 68.55 % of dried fish. The processed products were characterized with light brown color and acceptable fishy smell.